(untitled) (Research, Society and Development, 2022)
Violence in children is a global problem, which has intensified since the declaration of pandemic and the measures implemented by each state, this contributed to increased vulnerability in some groups, especially those who depend on adult care for their livelihood. This work is part of the results of the SAHAR Project - FCI 045-2019, the methodology used is descriptive, in which the categories caregiver kinship, disciplinary mechanisms, effectiveness and its repercussions are analyzed. Among the results of this work, women are identified as the gender of care represented in the mother, sister and grandmother, perceived as the best caregivers, in the same way the use of shouting, threats as a form of verbal violence and physical punishment with whips and other instruments (physical abuse), continue to be the most frequently used corrective methods, as for the repercussions, the caregivers identify physical injuries and few cases the parents identify emotional affectation and psychological damage. The conclusions highlight the need to train caregivers in effective, assertive and non-punitive disciplinary mechanisms for the construction of a society free of child violence.